Experts and decision making: first steps towards a unifying theory of decision making in novices, intermediates and experts - Britta Herbig; Andreas Glöckner (Max Planck Institute for Research on Collective Goods, 2009)
Expertise research shows quite ambiguous results on the abilities of experts in judgment and decision making (JDM) classic models cannot account for. This problem becomes even more accentuated if different levels of expertise are considered. We argue that parallel constraint satisfaction models (PCS) might be a useful base to understand the processes underlying expert JDM and the hitherto existing, differentiated results from expertise research. It is outlined how expertise might influence model parameters and mental representations according to PCS. It is discussed how this differential impact of expertise on model parameters relates to empirical results showing quite different courses in the development of expertise; allowing, for example, to predict under which conditions intermediates might outperform experts. Methodological requirements for testing the proposed unifying theory under complex real-world conditions are discussed.
Keywords: 330; Judgment and Decision Making; Expertise; Intermediate Effects; Parallel Constraint Satisfaction; Mental Representation; Entscheidung; Sachverständige; Beschränkte Rationalität; Kognition; Theorie